Measuring agenda-setting effects on Twitter during the 2016 UK EU referendum - Santos, T.; Louçã, Jorge; Coelho, H. (4th World Conference on Complex Systems (WCCS 2019), 2019)
This paper investigates first-level agenda-setting effects on Twitter during UK's EU referendum campaign. Using topic-modeling techniques, we investigate the dynamics of the interaction between users and the media content, and how the media outlets relate to each other. Results show that traditional media outlets dominated the debate, but alternative media played an important part. The media outlets that supported “Leave” stood closer to users' opinion who contributed to polarize the media's message, with pro-Leave side successfully framing some media's message in his own terms.